Acute Effect of a Protein Supplement on Targeted Plasma Amino Acid Profile among Healthy Asian Indians: A Randomized Controlled Trial. (1st June 2020) - Kurien, Ammu; Sharma, Nidhi; Marathe, Madhavi; Joshi, Nandan; Selvam, Sumithra; Devi, Sarita; Sambashivaiah, Sucharita
Abstract : Background . Indians have a poor protein intake in terms of quantity as well as quality because of their predominantly cereal-based diet. However, there is limited information on circulatory amino acid levels in healthy Indians. Herein, we evaluated the acute effect of a protein supplement on the plasma levels of essential amino acids (EAAs) in healthy Indian adults, using targeted EAA analysis. Methods . In this double-blind, randomized, crossover study, 20 healthy Indian adults were randomized to receive the test protein supplement (treatment arm, n  = 10) or placebo (control arm, n  = 10) with milk, after overnight fasting. After 7 days, the participants returned for the crossover treatment. Blood samples were collected at baseline and at 60 and 120 min after protein/placebo consumption. Plasma EAA levels were estimated using liquid chromatography-tandem mass spectrometry. Repeated measures ANOVA was performed to assess the effect of treatment on EAA levels. P values < 0.05 were considered statistically significant. Results . At baseline, mean plasma levels did not differ significantly between the two arms for any of the EAAs. In the treatment arm, the mean levels of all EAAs increased significantly from baseline to 60 min (P < 0.01 ), with no significant change from 60 to 120 min. There was no significant change in amino acid levels in the control arm. The magnitude as well as percentage of increase from baseline to 60 min was significantly greater in the treatment arm than in the control arm for all EAAs. Conclusion . Compared to placebo, protein supplement increased circulatory amino acid levels in healthy Indians. The observed increase in EAA levels and its role in conjunction with exercise in both healthy and diseased states need to be further evaluated. This is the first dataset exploring targeted EAA profiles and the effect of a protein supplement among healthy Indians. The clinical trial is registered with CTRI/2018/12/016777 .